An onboard ultra-rapid orbit determination strategy for LEO satellite utilizing spaceborne GNSS data - Peng Luo; Yezhi Song; Xiaogong Hu; Qingfeng Wu; Jianhua Yang; Kai Li; Chengpan Tang; Changshao Chen (Advances in Space Research, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

A novel biogas liquefaction process adopting dual nitrogen expansion cycle with carbon dioxide pre-cooling - Yanjun Huang; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Huaibin Li (International Journal of Refrigeration, 2026)

Synergizing early maturity and high yields through planting density and lodging-resistant strategy indica–japonica hybrid rice - Wenyu Jin; Lin Li; Qingfeng Song; Xinguang Zhu; Zhongwei Wei (Field Crops Research, 2026)

The Role and Potential Mechanism of Pectin and Pectin Oligosaccharides in Treating Intestinal Inflammation by Regulating Gut Microbiota - Qingfeng Zhang; Xiaoyu Wu; Jingyi Wang; Jiahao Miao; Cunyin Li; Shangyong Li; Ningning He; Jingyi Song (Probiotics and Antimicrobial Proteins, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Modelling of lake–land breeze circulation in a diurnal cycle - Qilong Zhong; Jiyun Song; Xiaoxue Wang; Jinhao Zhang; Qingfeng Zhang; Yuguo Li (Building and Environment, 2026)

New U-series and coupled ESR/U-series dating of Xujiayao (northern China), the type site for Homo juluensis - Qingfeng Shao; Fagang Wang; Junyi Ge; Jean-Jacques Bahain; Pierre Voinchet; Guilan Hu; Xinrui Jin; Rainer Grün; Christopher J. Bae; Xing Song (Quaternary Science Reviews, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

Characterisation of heavy metals and microbial communities in urban river sediments: Interactions and pollution origin analysis - Xuezheng Yu; Weiying Feng; Fanhao Song; Yunping Han; Qingfeng Miao; José Manuel Gonçalves (Environmental Research, 2025)

Electrospinning-mist polymerized antibacterial and super-hydrophilic nanofiber membrane for efficient dust filtration and enhanced comfort in mines - Gang Zhou; Liwei Jiang; Bo Wei; Pengjin Liu; Jiafa Du; Tingting Fan; Song Xin; Rulin Liu; Qingfeng Xu; Seeram Ramakrishna (Chemical Engineering Journal, 2025)

Review of biological algal fertilizer technology: Alleviating salinization, sequestering carbon, and improving crop productivity - Siyao Dai; Weiying Feng; Fanhao Song; Tingting Li; Yingru Tao; Fang Yang; Qingfeng Miao; Pengcheng Duan; Haiqing Liao; Haibin Shi; José Manuel Gonçalves; Isabel Maria Duarte (Bioresource Technology, 2025)

Multi-objective optimization of the plate-fin heat exchanger coupled with ortho-para hydrogen conversion for hydrogen liquefaction - Xiangkun Tao; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Hansheng Feng (International Journal of Refrigeration, 2025)

Corrigendum to ‘What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population?’ [Environ. Pollut. 345 (2024) 123499] - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2025)

Structural performance and design of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wei Li; Zhenhui Song; Fengbo Yu; Yun Niu; Hanyu Song (Ocean Engineering, 2025)

Occurrences, source apportionment, and potential risks of 55 progestins in surface water of the Yellow River Delta, China - Xiaoyan Shen; Qudi Zhang; Qingyue Xiang; Jiajun Zhao; Yue Cao; Kun Li; Jiayu Song; Zihao Wang; Xinkun Zhao; Qingfeng Chen (Journal of Hazardous Materials, 2024)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

A preliminary result for centralized autonomous orbit determination of gnss constellation and lunar satellite based on inter-satellite link measurements - Peng Luo; Ye-Zhi Song; Jianhua Yang; Xiaogong Hu; Chengpan Tang; Kai Li; Qingfeng Wu (GPS Solutions, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Modeling the Subpixel Land-Use Dynamics and Its Influence on Urban Heat Islands: Impacts of Factors and Scale, and Population Exposure Risk - Xun Liang; Song Guo; Chunyang Huang; Bingyu Wang; Yao Xiao; Jie He; Yang Li; Mengmeng Wang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Unrestricted region and scale: Deep self-supervised building mapping framework across different cities from five continents - Qiqi Zhu; Zhen Li; Tianjian Song; Ling Yao; Qingfeng Guan; Liangpei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population? - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2024)

Understanding the mediating role of labor out-migration in household income generation and distribution under a reforestation policy in rural China - Qi Zhang; Rajesh Bista; Richard E. Bilsborrow; Zhiqiang Zhang; Qingfeng Huang; Conghe Song (Journal of Environmental Management, 2023)

Improvement of non-fat yogurt gel syneresis by heat-unfolded whey protein isolate/mogrosides complexes: Effect on the structural characterization through simultaneous rheological and FTIR techniques - Qingfeng Ban; Zonghao Liu; Xuan Zhang; Bo Song; Yunqing Jiang; Jianjun Cheng (Food Hydrocolloids, 2023)

Sediment records of black carbon variations over the last two centuries in North China - Dejun Wan; Yongming Han; Lei Song; Dongliang Ning; Qingfeng Jiang (Science of The Total Environment, 2023)

Effects of load-related parameters on the dynamic response of concrete-filled double-skin steel tube K-joints under lateral impact loading - Qingfeng Yan; Jigang Zhang; Zhehao Ma; Feifei Liu; Guoliang Zhao; Chi Gu; Hanyu Song; Weicheng Zhang (Ocean Engineering, 2023)

Two-century sediment records of atmospheric mercury variations in North China and their relations with regional and global emissions - Dejun Wan; Handong Yang; Zhangdong Jin; Lei Song; Dongliang Ning; Longjuan Cheng; Qingfeng Jiang (Environmental Science and Pollution Research, 2023)

Melt blending crystallization regulating balanced nanodomains in efficient and scalable coating processed organic solar cells - Anran Wang; Yifei Kang; Chunqing Hou; Rong Li; Yilong Song; Qingfeng Dong (Science Bulletin, 2023)

Design, synthesis, antibacterial activity, and mechanism of novel resveratrol derivatives containing an 1,3,4-oxadiazole moiety - Ju Peng; Yong Zhang; Xing Liu; Yue Zou; Hongyi Song; Sheng Wang; Qingfeng Cai; Jixiang Chen; Deyu Hu (Pesticide Biochemistry and Physiology, 2023)

Phenological responses of Bactrocera dorsalis (Hendel) to climate warming in China based on long-term historical data - Pumo Cai; Yunzhe Song; Litao Meng; Jia Lin; Mengting Zhao; Qingfeng Wu; Chuanpeng Nie; Yanyan Li; Qinge Ji (International Journal of Tropical Insect Science, 2023)
It is well accepted that the phenology of insects whose life activities are closely related to temperature is changing in response to global climate warming. To investigate the impacts of climate warming on the phenology of Bactrocera dorsalis (Hendel) across large temporal and spatial scales, this study collected historical data on the occurrence and population dynamic of this pest in China, and systematically explored its phenological responses. The results showed a delayed trend for the dates of first occurrence, end occurrence, population initial growth, and population peak of B. dorsalis in China during 40 years, and the changes of the latter two phenological parameters were significant. The mean temperature in spring and summer were the key climatic factors affecting the occurrence and population growth of B. dorsalis in China, respectively. Moreover, the B. dorsalis data in eastern, southern, central, and southwestern China showed spatial heterogeneity of phenological responses to climate warming at a regional scale. B. dorsalis phenology and their changing patterns with climate warming varied by geographical location. This study provides valuable information for future monitoring, prediction, and prevention of the oriental fruit fly in the context of climate warming.

Experimental and numerical study on the dynamic behavior of concrete-filled double steel tubular T-joint under impact loading - Qingfeng Yan; Jigang Zhang; Feifei Liu; Zhehao Ma; Guoliang Zhao; Chi Gu; Hanyu Song; Yang Zhao (Ocean Engineering, 2023)

Discovery of quinazoline compound as a novel nematicidal scaffold - Yu Wang; Hongyi Song; Sheng Wang; Qingfeng Cai; Yong Zhang; Yue Zou; Xing Liu; Jixiang Chen (Pesticide Biochemistry and Physiology, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Targeted disruption of tyrosinase causes melanin reduction in Carassius auratus cuvieri and its hybrid progeny - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Jia Song; Junmei Liu; Wuhui Li; Yuqin Shu; Min Tao; Chun Zhang; Qinbo Qin; Jing Wang; Shaojun Liu (Science China Life Sciences, 2019)

Development of a Three-Dimensional Ray-Tracing Model of Sugarcane Canopy Photosynthesis and Its Application in Assessing Impacts of Varied Row Spacing - Yu Wang; Qingfeng Song; Deepak Jaiswal; Amanda P. de Souza; Stephen Patrick Long; Xin-Guang Zhu (BioEnergy Research, 2017)

Effect of mevalonic acid on cholesterol synthesis in bovine intramuscular and subcutaneous adipocytes - Xiaomu Liu; Wei You; Haijian Cheng; Qingfeng Zhang; Enliang Song; Fachun Wan; Hong Han; Guifen Liu (Journal of Applied Genetics, 2016)